Motion resistance in peripheral oxygen saturation monitoring using Biolight Analog SpO2 compared to Masimo SpO2: a non-inferiority study - Ting Yang; Yong Liu; FengHua Cai; Yong Li; Muhammad Saqib Mudabbar (BMC Anesthesiology)
Abstract Background Pulse oximeters are vital for assessing blood oxygen levels but can produce inaccurate readings during patient motion, leading to false alarms and alarm fatigue. Analog SpO2 Technology, which uses analog waveforms to filter motion artifacts, may improve accuracy compared to digital sensors. However, the effectiveness of this technology in reducing false alarms in clinical settings remains unclear. This study assesses and compares the motion resistance of Analog SpO2 Technology of two devices in the market. Methods Thirty healthy adults underwent controlled experiments (Control, Linear Motion, Angular Motion) using two pulse oximeters. Linear Motion tested hand displacement impact, while Angular Motion involved rhythmic hand motions at 120 bpm and 160 bpm. Results Both devices performed similarly in Control, with no disruptions. In Linear Motion, mild disruptions occurred, but no significant differences in SpO2 readings or alarms. Angular Motion at 120 bpm showed stability with no alarms. At 160 bpm, Device B (Biolight Analog SpO2) had fewer technical alarms but more SpO2 alarms than Device A (Masimo Analog SpO2). Conclusions Analog SpO2 exhibited motion resistance under static, linear and continuous waving angular motion up to 120 bpm and 160 bpm, but alarms occurred at 160 bpm with continuous tapping angular motion. These findings signify non-inferiority of either device in clinical settings. Further studies should include patients with cardiovascular and/or respiratory diseases. Trial Registration The study was submitted to and approved by the Biolight Ethics Committee (S0723), and written informed consent from all participants was obtained.